Cognitive Styles in Solving Educational Tasks - Galiakberova, Alfinur Azatovna; Galyamova, Elmira Khatimovna (Journal of History Culture and Art Research, 2019)
The article considers the influence of cognitive styles and individual features of perception and coding information on teaching geometry. Cognitive styles can determine success in learning, as they are manifested in the individual characteristics of the cognitive processes of students, their ways of perception, thinking, and action. Special attention is paid to the problems of connection of cognitive styles with interhemispheric brain asymmetry, level of intelligence, and motivation of a personality. The article underlines a very important for the learning process individual characteristic of a student. It is ‘differentiation of the field’, which means the influence of differences of the external environment on human decision-making. Differentiation of the field is described in terms of field dependence – field independence. Field dependence as a cognitive style means dominance of the whole, a lack of differentiation of parts in an image of perception, a disability to overcome the context, to select separate stimuli from the background. Field independence is an ability to resist the influence of conflicting background signs in the perception of visual forms and ties, an ability to perceive the whole, to allocate parts from complex figures, to choose stimuli from a context. In the conducted experimental research there were offered examples of tasks that allow to form cognitive ‘flexibility’ and overcome difficulties of students in analyzing geometric problems text. There were highlighted types of such tasks that were characterized by an educational effect. The conclusions from the experiment show that taking into account the parameters of cognitive styles with regular use of the system of developed tasks has a positive impact on the achievement of subject results in teaching students. The analysis of scientific and educational literature was carried out in order to make the understanding of the categories in this insufficiently researched area available to a wide range of school teachers.